2021
DOI: 10.1002/fes3.319
|View full text |Cite
|
Sign up to set email alerts
|

Application of bio and chemical fertilizers improves yield, and essential oil quantity and quality of Moldavian balm (Dracocephalum moldavica L.) intercropped with mung bean (Vigna radiata L.)

Abstract: Intercropping Moldavian balm with mung bean is an ecological approach for improving resource productivity. A field experiment was conducted over two growing seasons (2018 and 2019) to determine the effect of fertilizer application on yield and essential oil (EO) productivity of Moldavian balm intercropped with mung bean. The experiment had a two‐factor randomized complete block design (RCBD) with three replicates. The first factor comprised of five cropping patterns: Moldavian balm sole crop (MBs), mung bean s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 51 publications
(64 reference statements)
3
21
0
Order By: Relevance
“…A decrease in the weight of individual plants at higher plant density might be due to a reduction in the growth and development of the plants. The present result was in agreement with the finding of Faridvand et al (2021), who reported that basil benefited from the reduction of its companions and, with more access to light, it accumulated more chlorophyll and produced more aboveground biomass. Nigussie et al (2017) reported that the highest and lowest stem fresh weights were observed at 80% and 20% population density of rosemary intercropped with onion.…”
Section: Tomato-basil Intercropping Systemsupporting
confidence: 94%
“…A decrease in the weight of individual plants at higher plant density might be due to a reduction in the growth and development of the plants. The present result was in agreement with the finding of Faridvand et al (2021), who reported that basil benefited from the reduction of its companions and, with more access to light, it accumulated more chlorophyll and produced more aboveground biomass. Nigussie et al (2017) reported that the highest and lowest stem fresh weights were observed at 80% and 20% population density of rosemary intercropped with onion.…”
Section: Tomato-basil Intercropping Systemsupporting
confidence: 94%
“…The essential oils in fennel were analyzed using GC–MS (Agilent 7890/5975A GC/MSD), following the protocol of Faridvand et al (2021) 14 .…”
Section: Methodsmentioning
confidence: 99%
“…Intercropping can increase sustainable production and reduce chemical inputs in agricultural systems 12 14 , establish an ecological balance, exploit resources to a greater extent, increase yields quantitatively and qualitatively, and decrease the damage caused by pests, diseases, and weeds 15 , 16 . Therefore, reducing farmer reliance on pesticides while at the same time maintaining crop productivity and quality are key intercropping goals for sustainable farming.…”
Section: Introductionmentioning
confidence: 99%
“…According to referenced data from the literature about DMEO chemical composition ( Table 8 ), as well as cluster analysis performed using this data for the construction an unrooted phylogenetic tree ( Figure 4 ), it could be assumed that the largest number of accessions belonged to the geranial + neral + geranyl acetate chemotype [ 2 , 9 , 10 , 12 , 17 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The D. moldavica plants grown and utilized in this study also belonged to the above chemotype.…”
Section: Discussionmentioning
confidence: 99%